Human rights enjoyment in theory and activism - Ackerly, Brooke A. (Human rights review, 2011)
Despite being a seemingly straightforward moral concept (that all humans have certain rights by virtue of their humanity), human rights is a contested concept in theory and practice. Theorists debate (among other things) the meaning of “rights,” the priority of rights, whether collective rights are universal, the foundations of rights, and whether there are universal human rights at all. These debates are of relatively greater interest to theorists; however, a given meaning of “human rights” implies a corresponding theory of change and through that can be an important guide to the practice of human rights activists and their funders. In practice, any organization can describe their work as “rights based.” This article clarifies the practices of human rights activists and their funders that are consistent with a theory of human rights as (1) universal, (2) interdependent across groups and categories of people, (3) indivisible across issue areas and claims, and (4) measured by the enjoyment of rights.